2021
DOI: 10.1021/acs.inorgchem.0c03579
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Infrared Spectroelectrochemical Studies of CN-Substituted Bipyridyl Complexes of Ruthenium(II)

Abstract: Ruthenium(II) polypyridyl complexes [Ru(CN-Me-bpy) x (bpy) 3−x ] 2+ (CN-Me-bpy = 4,4′-dicyano-5,5′-dimethyl-2,2′-bipyridine, bpy = 2,2′-bipyridine, and x = 1−3, abbreviated as 1 2+ , 2 2+ , and 3 2+ ) undergo four (1 2+ ) or five (2 2+ and 3 2+ ) successive one-electron reduction steps between −1.3 and −2.75 V versus ferrocenium/ferrocene (Fc + /Fc) in tetrahydrofuran. The CN-Me-bpy ligands are reduced first, with successive one-electron reductions in 2 2+ and 3 2+ being separated by 150−210 mV; reduction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 47 publications
3
16
1
Order By: Relevance
“…In our study, a significant photoenhancement of the nitrile stretching vibration is observed for the MCLT excited state of 1 formed upon 400 nm excitation (Figure ). A similar enhancement has been observed for aromatic nitriles and CN substituted bipyridyl complexes of ruthenium­(II). , However, this is the first time that such an effect is reported for an intercalating probe. This enhancement serves to amplify the environmental response of the nitrile vibration, which is found to display a linear shift to the DMSO/water environment and builds on observations of the solution response of nitriles in the ground state …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In our study, a significant photoenhancement of the nitrile stretching vibration is observed for the MCLT excited state of 1 formed upon 400 nm excitation (Figure ). A similar enhancement has been observed for aromatic nitriles and CN substituted bipyridyl complexes of ruthenium­(II). , However, this is the first time that such an effect is reported for an intercalating probe. This enhancement serves to amplify the environmental response of the nitrile vibration, which is found to display a linear shift to the DMSO/water environment and builds on observations of the solution response of nitriles in the ground state …”
Section: Discussionsupporting
confidence: 80%
“…18 cm –1 from the position of the bleach ground state absorption, indicating the presence of a weaker CN bond in the 3 MLCT* excited state relative to the ground state. The downshift of the ν­(CN) has been previously observed for ruthenium polypyridyl complexes and is attributed to the population of a ligand based π* antibonding orbital, which weakens the ν­(CN) bonds. , …”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…In recent years, however, the investigation has expanded to other promising organic and inorganic systems including those containing boron [ 41 , 42 , 43 ], quinodimethane derivatives [ 44 , 45 ], metal-phtalocyanine [ 46 ], metal oxides-based film [ 7 , 47 , 48 ], oligoaniline [ 49 ], antracenes [ 50 , 51 ], azacenes [ 52 ], polymethine and polyimides [ 53 , 54 ], and some organometallic complexes [ 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Direct excitation of the substrates to their triplet excited states is spin-forbidden, and intersystem crossing from singlet to triplet excited states is frequently very inefficient in organic compounds; hence, metal-based triplet sensitizers are vital for many of these reactions . Iridium­(III) photosensitizers are often chosen due to their high triplet energies ( E T , up to 2.87 eV), long excited-state lifetimes, and their thermal and photostability. In recent years, photosensitizers based on earth-abundant metals have gained increasing attention, but many of them still require further development to become as widely applicable as their precious metal-based congeners, and until now, ruthenium­(II) and iridium­(III) sensitizers have remained the workhorses of synthetic photochemistry and applications in solar energy conversion. Against this background, the development of ruthenium­(II)- and iridium­(III)-based photosensitizers continues to be important. …”
mentioning
confidence: 99%